The Effect of Experiential Marketing and Emotional Marketing on Customer Loyalty in â€œLGSâ€ Showroom - Yacub, Rudi; Saleh, Khaerul; Putra, Maha (International Journal of Social Science and Business, 2022)
Along with rapid development of transportation, increasingly fierce competition also encourages business people to continue to innovate in making marketing strategies in order to attract customers attention and maintain customers loyalty. Customers not only appraise product and service based on its quality, but also through marketing strategies. Marketing strategies can be carried out aggressively through experiential approach and emotional approach to customers. This study aims to examine the effect of experiential marketing and emotional marketing on loyalty of LGS showroom customers. The sampling method used was non-probability sampling with purposive sampling type. The population in this study was 230 LGS showroom customers in the last three years. Meanwhile, the sample in this study was 70 LGS showroom customers who had made repeated purchases. The data collection conducted Â by distributing questionnaires. This study employed multiple linear regression data processing that had met the requirements of validity, reliability, and partial hypothesis testing t-test, with the Statistical Product and Service Solution program (SPSS version 24). This result found that experiential marketing and emotional marketing significantly affect customer loyalty in â€œLGSâ€ showroom